Myokine/Adipokine Response to “Aerobic” Exercise: Is It Just a Matter of Exercise Load? - He, Zihong; Tian, Ye; Valenzuela, Pedro L.; Huang, Chuanye; Zhao, Jiexiu; Hong, Ping; He, Zilin; Yin, Shuhui; Lucia, Alejandro (Frontiers in Physiology, 2019)
Purpose Exercise health benefits are partly mediated by exertional changes in several myokines/adipokines. This study aimed to compare the acute response of some of these biomarkers to aerobic exercise performed at the intensity corresponding to the maximum fat oxidation rate (FATmax) or the “anaerobic” threshold (AT). Methods Following a cross-over, counterbalanced design, 14 healthy untrained men (23 ± 1 years) performed a 45-min exercise bout at their FATmax or AT intensity (been previously determined through incremental exercise tests). The concentration of interleukin (IL)-15, follistatin, myostatin, fibroblast-growth factor (FGF)-21, irisin, resistin, and omentin was measured at baseline and 0, 1, 3, 24, 48, and 72 h post-exercise. Results AT exercise was performed at a higher intensity (85 ± 8 vs. 52 ± 14% of maximal oxygen uptake [VO2 max], p < 0.001) and induced a higher energy expenditure (p < 0.001) than FATmax, whereas a greater fat oxidation was observed in the latter (p < 0.001). A higher peak response of FGF-21 (+90%, p < 0.01) and follistatin (+49%, p < 0.05) was found after AT-exercise, as well as a trend toward a higher peak level of omentin (+13%, p = 0.071) and a greater decrease in resistin (−16%, p = 0.073). Conclusion Increasing exercise load (from FATmax to AT) results in a higher response of FGF-21, follistatin and omentin to aerobic exercise, with the subsequent potential cardiometabolic benefits. No effects were, however, observed on the remainder of biomarkers. Future research should address if manipulating other exercise variables (e.g., type, frequency) can promote a higher myokine/adipokine response.